DNA Polymerase-Associated Lectin (DPAL) and Its Binding to the Galactose-Containing Glycoconjugate of the Replication Complex. Issue 5 (October 1999) - Kelley, Thomas J.; Amand, Tara St.; Groll, Jeremy M.; Ray, Satyajit; Basu, Subhash
Abstract : The highly purified DNA Pol-α from rat prostate tumor (PA-3) and human neuroblastoma (IMR-32) cells appeared to be inhibited by Ricin (RCA-II), and Con-A. Loss of activity (40 to 60%) of a specific form of DNA polymerase from IMR-32 was observed when the cells were treated with tunicamycin [Bhattacharya, P. and Basu, S. (1982) Proc. Natl. Acad. Sci., USA 79: 1488–1492]. Binding of ConA and RCA to human recombinant DNA polymerase-α showed a specific labile site in the N -terminus [Hsi et al. . (1990) Nucleic Acid Res. 18: 6231–6237]. The catalytic polypeptide, DNA polymerase-α of eukaryotic origin, was isolated from developing tissues or cultured cells as a family of 180 to 120 kDa polypeptides, perhaps derived from a single primary structure. Immunoblot analysis with a monoclonal antibody (SJK-237-71) indicated that the lower molecular weight polypeptides resulted from either proteolytic cleavage of post-translational modification after specific cleavages. Present results suggest DNA polymerase-α from embryonic chicken brain (ECB) contains an α-galactose-binding subunit which may be involved in developmental regulation of the enzyme. It was shown before that the catalytic subunit of DNA polymerase-α reduces from 186 kDa in 11-day-old ECB to 120 kDa in 19-day-old ECB [Ray, S. et al. Cell Growth and Differentiation 2: 567–573] by the treatment with methyl-α-galactose. The low molecular weight DNA polymerase activity (120 kDa) can be reconstituted to high molecular weight ( M r = 186 kDa) with an α-galactose binding, 56 kDa lectin-like protein. Polyclonal antibodies raised against the purified lectin were able to precipitate DNA. Pol-α as determined by immunostaining with the polymerase-α-specific monoclonal antibody SJK 132-20, suggesting this is a DNA polymerase associated-lectin (DPAL). RCA-II and GS-I-Sepharose 4B chromatographies resulted in significant purification of DNA-α and a complete separation of polymerase complex and primase.